Rose Harbor : Sweet Tomorrows - Book 6 - Macomber, Debbie; King, Lorelei (New York, New York : Penguin Random House Audio Publishing, 2016)
The conclusion of the Rose Harbor series, set in the picturesque town of Cedar Cove and featuring Jo Marie Rose and handyman Mark Taylor, as a new set of guests check into the Rose Harbor Inn and find happily-ever-after.
Keywords: Cedar Cove (Wash. : Imaginary place) -- Fiction; Hotelkeepers -- Fiction; Bed and breakfast accommodations -- Fiction; Man-woman relationships -- Fiction; Female friendship -- Fiction; Audiobooks; Romance fiction